Developing of graphene oxide (GO) bio-filter for pathogenic bacterial control in farmed Asian clam, Corbicula fluminea. Issue 1 (May 2020) - Akrimah, Y; Mohd Zin, F A; An'amt, M N; Lee, S W; Aweng, E R
Abstract: Graphene oxide (GO) possess a potential as an antimicrobial agent in the aquaculture sector to substitute the role of antibiotic. Meanwhile, the consumption of Asian clam Corbicula fluminea has been gaining popularity throughout Malaysia in a line with the increasing cases of food poisoning caused by pathogenic bacteria resulted from the clam consumption. Thus, this experiment was conducted to investigate the potential of graphene oxide (GO) as an antibacterial filter in controlling pathogenic bacteria i.e. Escherichia coli, Salmonella spp., Vibrio spp. and coliform bacteria. A total of 180 clams were reared in both systems i.e. system installed with graphene oxide (GO system) and system with normal filter (Control system) for 2 weeks. Then, the bacteria were screened and enumerated from Asian clam tissue and farm water samples using total plate count (TPC) method and most probable number (MPN) method by comparing these two rearing systems. The results showed all isolated bacteria were 100 % reduced from farm water while coliform bacteria with 94% reduction in GO system. Conversely, bacteria reduction in clam tissue sample in GO system was varied and relatively low for coliform bacteria, Salmonella spp., total bacteria, Vibrio spp. as it reduced by 60.71 %, 31.38 %, 18.16 % and 1.34 %, respectively, while E. coli showed increasing bacteria count by 12.52 %. Therefore, it can be concluded that GO system is effective in reducing pathogenic bacteria in water compared to Asian clam tissue sample.